Investigating the Effect of Korean Red Ginseng on the Viability of Random-Pattern Skin Flaps in Rats. Issue 1 (July 2017) - Tekin, Hakan; Tekin, Gönül; Bulut, Gülay; Sargon, Mustafa Fevzi; Işik, Dağhan
Abstract : Objective: This experimental study investigated the efficacy of Korean Red Ginseng (KRG) extract in reducing the partial losses of random flaps. Method: Forty Wistar Albino rats were randomly distributed into 4 groups as (A) control group, (B) stress group, (C) oral KRG group, and (D) intraperitoneal KRG group. The modified McFarlane flap of 9 × 3 cm with a caudal pedicle was harvested from the back of the rats in all the groups. Korean Red Ginseng was administered to groups C and D at standard doses for 10 days. After 10 days, the flaps were removed in all groups and were examined macroscopically, histopathologically, histochemically, and biochemically. The results were statistically analyzed and compared among the groups. Results: The flap necrosis rates were significantly lower in groups C and D compared with groups A and B ( P < 0.05). The vascular density, antioxidant activity, and hypoxia-inducible factor-1α levels were significantly higher in the groups C and D compared with the groups A and B ( P < 0.05). Although vascular density, hypoxia-inducible factor-1α, and catalase levels were negatively correlated with the flap necrosis rates, there was a significantly positive correlation between malondialdehyde and necrosis rates. Conclusions: Korean Red Ginseng increases the viability of random pattern skin flaps, resulting in reduced rates of distal necrosis. Korean Red Ginseng has antioxidant activity and increases neovascularization.